Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1088/2041-8205/768/1/l11
|View full text |Cite
|
Sign up to set email alerts
|

NITROGEN ISOTOPES IN ASYMPTOTIC GIANT BRANCH CARBON STARS AND PRESOLAR SiC GRAINS: A CHALLENGE FOR STELLAR NUCLEOSYNTHESIS

Abstract: Isotopic ratios of C, N, Si, and trace heavy elements in presolar SiC grains from meteorites provide crucial constraints to nucleosynthesis. A long-debated issue is the origin of the so-called A+B grains, as for them no stellar progenitor has so far been clearly identified on observational grounds. We report the first spectroscopic measurements of 14 N/ 15 N ratios in Galactic carbon stars of different spectral types and show that J-and some SC-type stars might produce A+B grains, even for 15 N enrichments pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 35 publications
4
47
0
Order By: Relevance
“…1. The isotopic compositions of C, N, and Si of AB2 and MS SiC grains from this study are compared to literature data (Gyngard et al 2006;Hynes & Gyngard 2009) and observational data for J-and N-type carbon stars (Hedrosa et al 2013). For 14 N/ 15 N, the protosolar value of 441±5 reported by Marty et al (2011) is shown as a dash-dotted line for reference.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…1. The isotopic compositions of C, N, and Si of AB2 and MS SiC grains from this study are compared to literature data (Gyngard et al 2006;Hynes & Gyngard 2009) and observational data for J-and N-type carbon stars (Hedrosa et al 2013). For 14 N/ 15 N, the protosolar value of 441±5 reported by Marty et al (2011) is shown as a dash-dotted line for reference.…”
Section: Discussionmentioning
confidence: 82%
“…Low-mass CO novae and early R-and J-type carbon stars are all potential stellar sources of AB2 grains because they are enriched in 13 C and 14 N, and lack s-process enhancements according to astronomical observations and/or calculations (Dominy 1984;Abia & Isern 2000;Zamoro et al 2009;Jordi et al 2012;Hedrosa et al 2013). Both early R-and J-type carbon stars have near-solar metallicities, with the former being sparse in number (Zamora et al 2009) and the latter being abundant with higher 13 C and Li enrichments (10−15% of all carbon stars, Abia & Isern 2000).…”
Section: Potential Stellar Origin(s) Of Ab2 Grainsmentioning
confidence: 99%
“…Also, a significant change with respect to the line lists used in previous works is the updated CN line list in this spectral region. Details on how this CN list was computed can be found in Hedrosa et al (2013). The new CN line list has an impact on the global fitting of the observed spectra: theoretical fits are improved for most of the stars.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…The new solar abundance, log (F) = 4.40±0.25 3 , is significantly lower that the previous commonly adopted value 4.56 ± 0.30 (although it is in agreement within the error bars, Asplund et al 2009) and it is in a very good agreement with the meteoritic value, 4.46 ± 0.06 (Lodders et al 2009). Finally, Hedrosa et al (2013) provided a new CN line list that might affect the fluorine abundance determination in carbon-rich stars from the 2.3 μm region. As a consequence, in light of the new molecular parameters and solar fluorine abundance, a re-determination of fluorine abundances in AGB stars is needed to evaluate their actual contribution to the Galactic fluorine inventory.…”
Section: Introductionmentioning
confidence: 99%
“…This is so even when one assumes nitrogen isotopic ratios at stellar birth different than solar [15]. Very recently, spectroscopic observations of C and N isotopes in C-stars by [17] added more surprise to the already complex scenario. These authors indeed showed that isotopic ratios of these crucial elements at odds with stellar nucleosynthesis predictions, but similar to those observed in several presolar SiC grains, are present directly in the envelopes of some peculiar C-rich giants of types SC and C(J).…”
Section: Presolar Grains and Agb Processes I Intermediate Elementsmentioning
confidence: 99%